Analysis of Facilities and Infrastructure on the Quality of Learning of Students of Madrasah Aliyah Negeri 1 Samarinda School - Thaharoh Ananda Mumtahana; Helwilita; Ishaac, Muhamad (Chalim Journal of Teaching and Learning, 2024)
Facilities and infrastructure are essential components in supporting the learning process in education. Proper management of facilities and infrastructure ensures their optimal, effective, and efficient use during the learning process, which in turn contributes to improving the quality of education. Conversely, poor management of facilities and infrastructure can hinder an efficient learning process. For instance, a comfortable classroom with complete facilities allows students to focus and feel at ease during their studies. This study aims to describe the management of facilities and infrastructure and examine their impact on improving the quality of education. This qualitative research was conducted at MAN 1 Samarinda, with data collected through interviews, participant observation, and documentation. Data analysis was performed by collecting, organizing, interpreting the data, and presenting it in a narrative form before drawing conclusions. The results of this study reveal that the management of facilities and infrastructure at MAN 1 Samarinda plays a crucial role. In addition to facilitating various tasks, proper management also supports a smooth teaching and learning process, creating a safe, comfortable, and high-quality environment. This demonstrates that facilities and infrastructure are essential for both educators and students, particularly in efforts to enhance the quality of education.